The Minimal Impact of a Large-Scale Financial Education Program in Mexico City - Bruhn, Miriam (Elsevier, 2014)
We conduct randomized experiments around a large-scale financial literacy course in Mexico City to understand the reasons for low take-up among a general population, and to measure the impact of this financial education course. Our results suggest that reputational, logistical, and specific forms of behavioral constraints are not the main reasons for limited participation, and that people do respond to higher benefits from attending in the form of monetary incentives. Attending training results in a 9 percentage point increase in financial knowledge, and a 9 percentage point increase in some self-reported measures of saving, but in no impact on borrowing behavior. Administrative data suggests that any savings impact may be short-lived. Our findings indicate that this course which has served over 300,000 people and has expanded throughout Latin America has minimal impact on marginal participants, and that people are likely making optimal choices not to attend this financial education course.